ANALYSIS OF TECHNOLOGICAL INDICATORS OF TWO-LAYER KNITTED FABRICS OF THE NEW STRUCTURE - O`ralov Lazizbek Soyibnazar o`g`li; Jo`rabayev Abdurashid To`ramirzayevich (Journal Park Publishing, 2022)
In this article, 5 samples of two-layer knitted fabric with a new structure were woven on a Mayer knitting machine and its technological parameters were analyzed.
Keywords: Fabric, surface density, thickness, raw material, absolute volume, length, surface, polyester, front layer, back layer, yarn.